Modelling and control of a multi-stage interleaved DC-DC converter with coupled inductors for super-capacitor energy storage system - De, Dipankar; Klumpner, Christian; Patel, Chintanbhai; Kulsangcharoen, Ponggorn; Rashed, Mohamed; Asher, Greg (IET, 2013)
Interleaved converters with coupled inductors are widely used to share load current in high power applications. It offers high equivalent switching frequency and reduced output current ripples using small size magnetic components. Due to smaller common-mode inductance, control system can be designed to achieve fast dynamic response. This paper proposes 8 channel interleaved DC/DC converter for interfacing super-capacitor energy storage system to a 400V DC voltage bus. Multi-stage interleaving magnetic circuit with two-phase coupling inductor as a building block is proposed. A methodology is developed to construct the model of the multi-stage magnetic circuit from the basic two-phase coupled inductor model. The derived model is successfully used to evaluate the system power losses and to design the magnetic circuit parameters and its current controller to fulfil the DC/DC converter steady state and dynamic performance specifications. A 20kW/four stage/8 channel DC/DC converter laboratory prototype has been built to connect a super-capacitor stack to 400V DC voltage bus. Experimental investigation validates the modeling, the system losses calculations and the design specifications of the system.